HEGEMONI DAN KONTRA-HEGEMONI DALAM RUANG REDAKSI: ANALISIS WACANA KEBIJAKAN DESK BAHASA TEMPO TERHADAP STANDAR JURNALISTIK - Mikail Randu Rayyana; Endang Sholihatin (STKIP Subang, 2026)
This study explores the strategic role of the Language Desk (Desk Bahasa) within Tempo’s newsroom as an instrument of both hegemony and counter-hegemony. The central problem addressed is the inherent tension between journalists' individual writing styles and institutional standards, alongside the tendency of contemporary mass media to succumb to bureaucratic euphemisms and ambiguous political language. This research aims to deconstruct how the Language Desk's linguistic interventions function to maintain the integrity of critical journalism and the institution's linguistic sovereignty. Utilizing a qualitative methodology, the study applies Norman Fairclough’s Critical Discourse Analysis (CDA) integrated with M.A.K. Halliday’s Systemic Functional Linguistics (SFL). Primary data were gathered through a comparative text analysis of raw news drafts and finalized edited manuscripts across three distinct categories: socio-religious affairs, human-interest events, and law/corruption. The findings reveal that the Language Desk acts as an